Metalicidad de estrellas con exoplanetas y discos de polvo - Petrucci, Romina Paola (2011)
We present an uniform comparison among three different kind of objects: cool-Jupiter exoplanet host-stars, stars with dust disks and exoplanet host-stars with dust disks. The goal of this contribution was to determine why stellar objects originally surrounded by planetesimals evolve to different final configurations, from stars with planets to stars with debris disks.